استخدام الدليل الإلكتروني لإثبات جرائم التزوير: دراسة مقارنة بين الإمارات العربية المتحدة ومصر - عبير أحمد محمد الحميري
The study aims to investigate the use of electronic evidence to prove forgery offences through a comparative analysis of the UAE and Egypt. In the study, the researcher used the analytical technique, the comparative method, and the inductive approach. The study's dilemma is shown by the key question, which is: How is electronic evidence utilized to establish forgery offences in UAE and Egyptian legislation? The study yielded several conclusions, the most noteworthy of which was that the UAE legislator was eager to produce legislative texts that combat electronic forgery offences since it offered legal protection to electronic papers and signatures. It is also set its rules and regulatory frameworks, with the most visible example being the UAE legislator's outlawing of electronic forgery via Article No. (6) of Decree-Law No. (5) of 2012 on combatting information technology crimes. Furthermore, the study's findings demonstrated that Egyptian legislators have addressed information crimes by developing legislative control systems and issuing new punitive legislative texts, such as Law No. (175) of 2018 and its executive regulations No. (1699) of 2020, which were issued to combat information technology crimes. Furthermore, the study's findings revealed that, from the standpoint of Islamic law, restricting the methods of proof to certain subjects does not allow for growth in safeguarding plaintiffs' rights in establishing their cases. As a result, the researcher made the following recommendations: The necessity for lawmakers in both the UAE and Egypt to adopt a particular legislative rule that handles procedural issues linked to the crime of electronic forging. Furthermore, the researcher recommends that both UAE and Egyptian legislators consider the distinct nature of electronic forgery from traditional forgery, which necessitates the development of a special law to define the acts that fall under the term electronic forgery. The advantage of the research will help to establish future visions and frameworks for national, legislative, and administrative initiatives to combat electronic forgery in both the United Arab Emirates and the Arab Republic of Egypt.